1999
DOI: 10.1046/j.1440-1754.1999.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparotomy for necrotizing enterocolitis: Intensive care nursery compared with operating theatre

Abstract: The use of the neonatal intensive care nursery for surgery on neonates weighing less than 1500 g with severe NEC can be justified and such use should be encouraged. In contrast, secondary transport of neonates weighing less than 1500 g to the OR for laparotomy is associated with significant deterioration in a number of physiological parameters, which may impact on morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…However, Frawley et al carries out all surgery on NEC infants under 1500 grams in the neonatal intensive care unit, and reports a mortality rate of 33% [17]. Hall et al report that they routinely intubate, ventilate and operate on all neonates in the neonatal intensive care unit [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, Frawley et al carries out all surgery on NEC infants under 1500 grams in the neonatal intensive care unit, and reports a mortality rate of 33% [17]. Hall et al report that they routinely intubate, ventilate and operate on all neonates in the neonatal intensive care unit [18].…”
Section: Discussionmentioning
confidence: 99%
“…Data indicating that outcomes are worse if infants with necrotizing enterocolitis are transferred for surgery, rather than operated on in the NICU, may be dismissed as being rather historical but very recent data from Michigan examining transports of very low birth weight (VLBW) infants, that is, <1500 g, using a previously validated transport risk index of physiologic stability (‘TRIPS’), confirm the previous historical findings of real deterioration in these infants . This latter study identified that increased transport times of only greater than 15 min were associated with increased morbidity.…”
Section: The Case For Operating In the Nicumentioning
confidence: 99%
“…For some years now, there has been a controversy concerning the best site to perform operations in sick and unstable neonates . The challenge still remains for a surgical team to perform a matched control study as this has not been achieved to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es scheint vorteilhaft, wenn es die lokale Logistik erlaubt, extrem unreife oder schwer kranke Kinder nicht zu transportieren, sondern sie auf der Intensivstation zu operieren. Es konnte allerdings kein Unterschied in der Mortalität gezeigt werden [27]. Transporte in den Operationssaal sind v. a. mit ausgeprägteren Hypothermien [4], Operationen an der Intensivstation wahrscheinlich mit mehr Infektionskomplikationen verbunden [40].…”
Section: Spezielle Betrachtungen Bei Extrem Frühgeborenenunclassified